Considering phrasal verbs and collocations for ESL vocabulary teaching / Brandon Chai An Weng - Weng, Brandon Chai An (Universiti Teknologi MARA, Sabah, 2020)
Words have a habit of appearing in recurrent patterns. These recurring patterns may take the form of phrasal verbs, collocations, and other multi-word expressions (MWEs). Since these patterns constantly re-occur in both speech and writing, it would seem prudent to teach vocabulary to ESL learners in the manner in which words actually present themselves: in typical chunks. A common example of such a chunk would be "to deal with the problem", in which "deal with" and "problem" are collocates. This paper contains three sections. The first examines what phrasal verbs and collocates are in the first place, and why they are particularly important for learners. The second part is a review of recent studies that support the teaching of MWEs and chunking pedagogy. This paper concludes by discussing the potential of incorporating chunking pedagogy in one's own ESL vocabulary teaching.